Respon Al-Qur'an terkait fenomena domestifikasi perempuan - Karomah, Maulidatul Lailatul (Maliki Interdisciplinary Journal, 2024)
The domestication of women is an important issue in society. It is related to the role and nature of women in the domestic sphere. In societies adhering to patriarchal norms, women are often placed in role as homemakers and maintainers of social relationship within the domestic environment. The household role of women is often undervalued. The rigid division of roles between men and women at home often means that domestic work is seen as less valuable compared to men’s work in the public sphere. Altough many women choose to stay at home and care for their children, many men are responsible for earning a living outside the home. The division of household and public duties is intended to achieve harmony within the household, but this can change depending on circumstances. For example, if social conditions push women to work outside the home to support the family, or if men are unable to work, then there is a need to readjust the division of household and public responsibilities. Household chores are not solely the responsibility of women, and public work is not necessarily only the responsibility of men.